Transformasi Pembelajaran Pendidikan Agama Islam Melalui Media Interaktif Berbasis Kecerdasan Buatan di Era Digital - Asrori, Achmad (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
This study aims to analyze the effectiveness of interactive media based on artificial intelligence (AI) in improving the quality of Islamic religious education (IRE) learning in the digital era. The research employs a qualitative empirical approach conducted at UIN Raden Intan Lampung. Data were collected through in-depth interviews, observations, and documentation involving students and lecturers directly engaged in AI-based learning processes. The findings show that using AI-based interactive media significantly enhances students' learning outcomes through adaptive and personalized learning approaches, making IRE material easier to understand and more relevant to the needs of millennial and Gen Z learners. Furthermore, AI media successfully increases students’ motivation by providing an interactive, enjoyable, and visually engaging learning experience, which has been a significant challenge in traditional religious education. Positive perceptions from students and lecturers strengthen the effectiveness of technology as a learning aid. However, the successful implementation of AI media heavily depends on technological infrastructure readiness, as well as the competence and support of educators. However, the study also identifies several significant obstacles, such as limited technology access and teacher training, which remain substantial challenges in using AI-based interactive media in educational settings. Therefore, maximizing the potential of AI-based interactive media in IRE learning requires collaborative efforts from multiple stakeholders, including the development of technological infrastructure, intensive teacher training, and policy support that promotes the integration of technology in religious education—so that this media not only enhances cognitive aspects but also contributes to affective and psychomotor learning dimensions in the digital age.